Population genetics considerations - Laird, Nan (Henry Stewart Talks, 2007)
Population genetics: definitions and terminology, Genetic association, Association between disease and a gene, Linkage equilibrium/disequilibrium, Hardy-Weinburg equilibrium/disequilibrium, Population inbreeding, Population substructure, Bias and variance inflation in genetic association tests, Genomic control
Reviewed at 2015/09/23